Micro Finance Services and Poverty Eradication: A Case Study of Mparo Town Council Rukiga District. - Akankunda, Racheal (Kabale University, 2024)
The research focused on “the role of microfinance services on poverty eradication” specifically Mparo Town Council Rukiga district as a case study. The research study was guided by three objectives; to establish the role of microfinance on poverty eradication in Mparo Town Council Rukiga, to find out whether sensitization of people is helping to improve the income level and hence reducing poverty in Mparo Town Council Rukiga, and to establish the relationship between microfinance services and eradication in Mparo Town Council Rukiga. The researcher used questionnaires and observation as methods of collecting primary data. The findings of the study revealed that microfinance services included loan disbursement, loan repayment, loan size, loan usage, and interest rate. Poverty eradication included household performance, business performance, individual empowerment, and household income. The study concluded that microfinance services play the roles in Mparo town council Rukiga District that include lending money to individuals and groups, safeguarding people’s cash, uniting them, and encouraging them to save. The study recommended that government should support microfinance services to offer better services mostly in Mparo town council Rukiga District. The government should also set up credit facilities that should be freely accessed by microfinance services in order to improve the rate at which they offer their services and the clients should greatly access services offered by microfinance services so as to get credit facilities that help them to reach financial support.